Juniper Gredos A new prickly juniper edaphoxerophytic relict community (Juniperus badia, Cupressaceae) from the Tiétar valley (Gredos range, Iberian Central System, Ávila, Spain) - López-Sáez, José Antonio; Sánchez-Mata, Daniel (Mediterranean Botany, 2025)
A new community is proposed for the checklist of Iberian Peninsula vegetation: Erico arboreae-Juniperetum badiae. This forest vegetation type is described from rocky landscapes of the southern slopes of the Gredos range (Tiétar valley, Ávila) having an edaphoxerophilous and relict character.